Mind the gap: Health reporting in the Pacific - Trevor Cullen (Asia Pacific Network, 2014)
Previous research on developing health journalism in the Pacific region has encouraged journalists to think outside the box when it comes to reporting health, and to view it as more than just drugs and doctors. Factors such as politics, economics, religion, education, gender inequality and traditional cultural taboos influence health outcomes to varying degrees. This perspective on health provides an extensive list of news and feature stories for the media, and yet, this wider focus on the determinants of health is not what drives health journalism in many Pacific countries. This article uses a case study of press coverage of HIV in Papua New Guinea from 2000 2010 to show how coverage of HIV or other communicable diseases in the Pacific need a much wider frame than that of drugs and doctors.